(untitled) (Mugda Medical College Journal, 2023)
Background: Pemphigus vulgaris (PV) is an autoimmune bullous disorder characterized clinically by blisters and erosions of the skin and/or mucous membranes. Serum prolactin plays a role in the pathogenesis of pemphigus vulgaris. Objective: The study aims to observe the serum prolactin concentration in patients with pemphigus vulgaris. Methods: This cross-sectional study was conducted at the Department of Dermatology & Venereology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between May 2017 and April 2018. A total of 35 patients were included in the study. A consecutive type of sampling technique was used. The dermatological examination was done to ascertain the extent of involvement of the disease. Results: Among 35 patients, 31.4% belonged to 30-50 years age group, while 62.9% belonged to >50 years and 5.7% patients belonged to <30 years ae group. The mean age was found 42.7±11.8 years with ranged from 19-65 years. The majority of the patients (57.1%) were male, and 42.9% patients were female. It was observed that 30(85.7%) had vesicles, 25(71.4%) had bulla, 35(100%) had erosions and 6(17.1%) had other types of lesions. 28 patients (80.0%) had scalp, 32(91.4%) had extremity, 35(100.0%) had trunk and 31(88.6%) had mucous membrane as the sites of involvement. The mean duration of disease was 9.0±12.7 months with a range from 0.5 to 36 months. It was observed that 9 patients (25.7%) had hyperprolactinemia, while 26 patients (74.3%) had normal levels of prolactin. The mean serum prolactin level was found 28.7±16.7 ng/ml with a range from 1.64 to 51.04 ng/ml. Conclusion: Since serum prolactin plays a role in the pathogenesis of pemphigus vulgaris, it may offer a novel therapeutic target for treatment of PV. Thus, we may reduce morbidity and mortality rate in PV patients by modifying their serum prolactin levels. Mugda Med Coll J. 2023; 6(1): 20-24